Investors' Portfolio Behavior under Alternative Models of Long-Term Interest Rate Expectations: Unitary, Rational, or Autoregressive - Friedman, Benjamin M.; Roley, V. Vance (Econometrica, 1979)
Benjamin M. Friedman, V. Vance Roley, Investors' Portfolio Behavior under Alternative Models of Long-Term Interest Rate Expectations: Unitary, Rational, or Autoregressive, Econometrica, Vol. 47, No. 6 (Nov., 1979), pp. 1475-1497